A Study on Energy of Fuzzy Graphs - Sangale, Suryabhan A.; Ahire, Kailas S. (Communications in Mathematics and Applications, 2025)
We study various types of fuzzy networks and techniques to energy computation.We disclose novel results on energy distribution in specific fuzzy graph classes, namely fuzzy complete and fuzzy bipartite graphs. The design of the matching crisp graph and the degree of fuzziness have a significant impact on the energy of fuzzy graphs. In addition, we provide new methods that are optimized for large-scale fuzzy network energy calculations. These results enhance our understanding of fuzzy graph energy dynamics and provide insight on potential applications of fuzzy graphs in network optimization and analysis.
Keywords: Fuzzy graph; Energy of fuzzy graph; Spectral radius energy